Climate Change as a Threat to Peace Impacts on Cultural Heritage and Cultural Diversity - Schorlemer, Sabine von; Maus, Sylvia (Dresden Papers on Law and Policy of the United Nations, 2015)
This volume takes a fresh look at climate change as a threat to peace and its impacts on cultural heritage and cultural diversity. It proceeds under the assumption that the impacts of climate change on cultural heritage and cultural diversity may challenge sustainable global peace. As innovative feature, the interdisciplinary nexus between cultural heritage and peace is explicitly taken account of. Accordingly, corresponding threats on climate change and conflict on the one hand, and protection of cultural property and climate change on the other, are pulled together into one conceptual triangle. While the importance of the protection of cultural heritage in armed conflicts tends to become more and more recognized, the crucial role of cultural policy as a reconciliatory, proactive element of building and securing of sustainable peace has so far been largely underestimated.